Processing - Booth, Tara (Drawn & Quarterly, 2024)
"Known for her buzzing colors, delightful patterns, sharp humor, and unflinching vulnerability, Tara Booth does not miss any mark in this exquisitely woven collection of pure and nasty magic. Part advice column and exhibit, exploration of psychic pollution and tranquility, processing is-quite simply-intrepid: in its honesty; its unapologetic grossness; its unrivaled and frank portrayal of life with a body that bleeds. In the grand tradition of underground women cartoonists like Julie Doucet and Aline Kominsky-Crumb, Booth draws a horned up woman laying rose petals on the bed, to distract from the bedbugs before her hookup arrives. She bears witness to the reality of wearing a t-shirt with no bra-when you stretch, your boobs, sometimes,pop right out. This is all just life but we don't often see it on the page. Undaunted, Booth draws it. When advice from spiritual guruslike Tara Brach and Ram Dass just aren't cutting it, take solace inthe genuine arms of Tara Booth: a fearless cartoonist who is unafraid to put her existential angst, blemishes, and stains right on the page, and who-with relentless relatability-makes us all feel a bit more at home in our too-human vessels. With color that vibrates and fluids that impose, Processing lays Booth bare-literally and figuratively"--